REPRESENTASI HUBUNGAN ALAM DAN MANUSIA DALAM KUMPULAN PUISI MATA BADIK MATA PUISI KARYA D. ZAWAWI IMRON (KAJIAN EKOKRITISISME) - Yuriananta, Renda (University of Brawijaya, 2018)
Ecocriticism is a new science for the development of literature. Ecocriticism examines literature by revealing how the relationship of literature to the physical environment (nature). Mata Badik Mata Puisi is an anthology of poetry by D. Zawawi Imron which is thick with natural nuance. The anthology of the poem is dissected using the study of ecocriticism. From the analysis process found that Zawawi Imron put the position of nature as the center of life, unlike other authors who place humans as axis. There are three findings from the analysis, namely the representation of nature as the center of life, balance and imbalance of nature, and nature as a teacher that shows the direction of life. These three findings are based on the study of ecocriticism on the anthology of the Mata Badik Mata Puisi. Thus, it can be concluded that Zawawi Imron tried to raise environmental issues on the anthology of the poem.